Determinants of Uterine Rupture and Its Management Outcomes among Mothers Who Gave Birth at Public Hospitals of Tigrai, North Ethiopia: An Unmatched Case Control Study - Meresa Berwo Mengesha; Desta Abraha Weldegeorges; Yared Hailesilassie; Weldu Mammo Werid; Mulu Gebretsadik Weldemariam; Fissaha Tekulu Welay; Senait Gebreslasie Gebremeskel; Berhanu Gebresilassie Gebrehiwot; Hagos Degefa Hidru; Hirut Teame; Haftay Gebremedhin; Natnael Etsay Assefa (Journal of Pregnancy)
Introduction. Uterine rupture is a leading cause of maternal death in Ethiopia. Despite strengthening the health care system and providing basic and comprehensive emergency obstetric care closer to the communities, uterine rupture continues to produce devastating maternal and fetal outcomes. Although risk factors of uterine rupture are context specific, there is lack of clarity in our context towards the contributing factors and untoward outcomes of uterine rupture. This study was conducted to identify the risk factors of uterine rupture and its impacts in public hospitals of Tigrai. Objective. This study would identify determinant factors of uterine rupture and its management outcomes among mothers who gave birth in public hospitals in Tigrai region, North Ethiopia. Method. A retrospective hospital-based unmatched case control study design was implemented with 135 cases of women with uterine rupture and 270 controls of women without uterine rupture. Cases were enrolled consecutively from case notes of women who gave birth from 1/9/2015 to 30/6/2019, while charts (case note) of women without uterine rupture found following the cases were selected randomly and enrolled. Bivariate and multivariate logistic regression with 95% confidence interval was used to identify the determinants of uterine rupture. Result. Mothers referred from remote health institutions (AOR 7.29 (95% CI: 2.7, 19.68)), mothers who visited once for antenatal care (AOR 2.85 (95% CI: 1.02, 7.94)), those experiencing obstructed labor (AOR 13.33 (95% CI: 4.23, 42.05)), and birth weight of a newborn greater than four kilograms (AOR 5.68 (95% CI: 1.39, 23.2)) were significantly associated with uterine rupture. From 135 mothers who develop uterine rupture, 13 (9.6%) mothers died and 101 (74.8%) fetuses were stillborn. Obstetrical complications like abdominal hysterectomy in 75 (55.6%) of mothers and excessive blood loss in 84 (57.8%) were additional untoward outcomes of uterine rupture. Conclusion. Referrals from remote health institutions, once-visited antenatal care, obstructed labor, and birth weight of newborns greater than four kilograms were significant determinants of uterine rupture. Maternal death, stillbirth, hysterectomy, and hemorrhage were adverse outcomes. The findings of this study suggest early identification of factors that expose to uterine rupture during antenatal care, labor, and delivery must be attended to and further prospective studies are needed to explore predictors of untoward outcomes. Knowing the determinants of uterine rupture helps prevent the occurrence of a problem in pregnant women, which reduces maternal morbidity and mortality, and would have a tremendous help in identifying the best optional strategies in our current practices. This assertion was added to the abstract concluding session.